A Study On Awareness And Perception Among Community Regarding Vitamin-A Prophylaxis Programme - Das J.K; Murali I (Wolters Kluwer Medknow Publications, 1993)
A total of 714 mothers of 986 pre-school children of a subcentre area of primary health center dankaur of Bulandshahr district in Uttar Pradesh were interviewed to assess their knowledge regarding dietary sources of vitamin-A and signs and symptoms of its deficiency. Only 160 were aware of the relationship between diet and eye problems and of them only 105 mothers could enumerate the actual vitamin-A rich diets. While 315 respondents were familiar with night blindness and xerophthalmia, only 160 actually knew that vitamin-A deficiency causes these problems and 156 had correct knowledge about the remedial measures. Regarding the perception about the existing vitamin-A prophylaxis programme 78(10.9%) mothers surveyed were aware of this.